Step
*
of Lemma
biject-int-nat
∃f:ℤ ⟶ ℕ. Bij(ℤ;ℕ;f)
BY
{ (With ⌜λx.if 0 ≤z x then 2 * x else (2 * ((-x) - 1)) + 1 fi ⌝ (D 0)⋅
THEN Auto
THEN RepeatFor 2 (D 0)
THEN Reduce 0
THEN Auto) }
1
1. a1 : ℤ
2. a2 : ℤ
3. if 0 ≤z a1 then 2 * a1 else (2 * ((-a1) - 1)) + 1 fi = if 0 ≤z a2 then 2 * a2 else (2 * ((-a2) - 1)) + 1 fi ∈ ℕ
⊢ a1 = a2 ∈ ℤ
2
1. b : ℕ
⊢ ∃a:ℤ. (if 0 ≤z a then 2 * a else (2 * ((-a) - 1)) + 1 fi = b ∈ ℕ)
Latex:
Latex:
\mexists{}f:\mBbbZ{} {}\mrightarrow{} \mBbbN{}. Bij(\mBbbZ{};\mBbbN{};f)
By
Latex:
(With \mkleeneopen{}\mlambda{}x.if 0 \mleq{}z x then 2 * x else (2 * ((-x) - 1)) + 1 fi \mkleeneclose{} (D 0)\mcdot{}
THEN Auto
THEN RepeatFor 2 (D 0)
THEN Reduce 0
THEN Auto)
Home
Index